Analytical investigations closer to the patient. Issue 6232 (5th July 1980) - Watson, D
Abstract : Do-it-yourself bioanalytical equipment that requires no analytical skill to operate is currently available for use in intensive care units, operating suites, side wards, health centres, clinics, general practitioners' surgeries, etc. Agreement is needed between the laboratory consultant and doctors and others using laboratory-type equipment and reagents in near-bedside analyses for diagnosis, clinical management, or health screening of their patients. Choice and safety of method procedure, operator training and accountability, quality control and assessment, maintenance, safety and future development of do-it-yourself equipment must be considered.